Developmental axon degeneration requires trpv1-dependent Ca 2+ influx - Johnstone, Aaron D. (2019)
Development of the nervous system relies on a balance between axon and dendrite growth and subsequent pruning and degeneration. The developmental degeneration of dorsal root ganglion (DRG) sensory axons has been well studied in part because it can be readily modeled by removing the trophic support by nerve growth factor (NGF) in vitro. We have recently reported that axonal fragmentation induced by NGF withdrawal is dependent on Ca2+, and here, we address the mechanism of Ca2+ entry required for developmental axon degeneration of mouse embryonic DRG neurons. Our results show that the transient receptor potential vanilloid family member 1 (TRPV1) cation channel plays a critical role mediating Ca2+ influx in DRG axons withdrawn from NGF. We further demonstrate that TRPV1 activation is dependent on reactive oxygen species (ROS) generation that is driven through protein kinase C (PKC) and NADPH oxidase (NOX)-dependent pathways that become active upon NGF withdrawal. These findings demonstrate novel mechanistic links between NGF deprivation, PKC activation, ROS generation, and TRPV1-dependent Ca2+ influx in sensory axon degeneration.